An Innovative and Cost-Effective Solution for Livestock Waste Management in China, Thailand and Vietnam - Roos, Kurt (World Bank, Washington, DC, 2014)
The East Asia region is home to more than half the world s stock of pigs and more than one-third of the world s poultry a population that is expected to grow rapidly over the next decades. As a result, about 26 percent of the total area in East Asia suffers from significant nutrient surpluses, mainly from agricultural sources. For instance, the region has a 47 percent surplus of phosphorus and a 16 percent surplus of nitrogen, both from animal manure. This contributes significantly to the degradation of regional water quality. To address this issue, the Global Environment Facility (GEF) funded the Livestock Waste Management in East Asia (LWMEA) Project. This smart lesson discusses major challenges faced and key lessons learned from implementing that regional project.